Probiotic Application of Bacteriocin-Producing S. Epidermidis in A Cellulosic Pad to Treat Some Skin Infections - Hussein, Yasser Ali; Luti, Khalid Jaber Kadhum (Iraqi Journal of Science, 2020)
The aim of this study was to evaluate the possibility of using Staphylococcus epidermidis cells as a probiotic to treat some skin infections. For this purpose, S. epidermidis Y73, which is an active bacteriocin producer and non-biofilm forming isolate, was selected among 134 skin isolates through primary and secondary screening. Tryptic soya broth was selected as the best medium to support bacteriocin production, while the optimal pH and temperature for S. epidermidis Y73 growth were 7 and 37Â°C, respectively, which were invested in the formula preparation. Furthermore, the possibility of using this isolate as a probiotic was investigated by preparing 4 potential cellulosic pads with 4 different formulae which were all subjected to an in vitro trial to select the one which is superior to the others in terms of supporting bacteriocin production and cells viability. The shelf life of the pad was estimated and the results showed that the cells remained vital until the 20th week. The selected pad formula was used to treat artificially induced wounds on rabbit skin. The wounds were infected with Staphylococcus aureus, Kocuria rosea and Pseudomonas. aeruginosa. The symptoms in both control and treated animals were recorded and, based on the results; the healing process with the presence of the S. epidermidis Y73 pad was significantly faster compared with that for the control. This research will serve as a base for future studies on using vital cells of S. epidermidis as probiotics and, hence, make a contribution to the current literature on using live cells to treat bacterial skin infections.